(untitled) (Acta Scientiarum. Health Sciences, 2014)
Self-rated health is a major health indicator and has been widely used in epidemiologic surveys. Current study analyzes the factors associated to regular and negative self-rated health in Brazilian college students. Current investigation is a segment of the 2010 MONISA study carried out in a Brazilian public university with 5,461 students. Estimated sample comprised 1,232 university students and results showed self-rated regular and negative health. Multinomial logistic regression estimated Odds Ratio (OR). The factors associated to regular health self-evaluation negative assessment of relationship with professors (OR: 1.85; CI95%: 1.20-2.87); inactivity in leisure (OR: 2.34; CI95%: 1.73-3.16); insufficient consumption of vegetables; almost daily consumption of soft drinks; assessment of intermediate and negative stress (OR: 3.34; CI95%: 2.11-5.28). Students inactive in leisure (OR: 2.37; 95%CI: 1.09-5.13), students with self-evaluated negative stress (OR: 10.1; 95%CI: 3.23-31.8) and obese students (OR: 4.52; 95%CI: 1.36-15.0) were associated to the negative health self-assessment. It has been verified that health behavior is rather associated to the regular self-assessment of health, whereas perceptive and biological indicators were more associated to negative health self-assessment.